ADP-dependent glucokinase regulates energy metabolism via ER-localized glucose sensing - Imle, Roland; Carl, Matthias; Himmelreich, Nastassja; Thiel, Christian; Gröne, Hermann-Josef; Poschet, Gernot; Völkers, Mirko; Gülow, Karsten; Kölker, Stefan; Sauer, Sven (Scientific reports, 2019)
Modulation of energy metabolism to a highly glycolytic phenotype, i.e. Warburg effect, is a common phenotype of cancer and activated immune cells allowing increased biomass-production for proliferation and cell division. Endoplasmic reticulum (ER)-localized ADP-dependent glucokinase (ADPGK) has been shown to play a critical role in T cell receptor activation-induced remodeling of energy metabolism, however the underlying mechanisms remain unclear. Therefore, we established and characterized in vitro and in vivo models for ADPGK-deficiency using Jurkat T cells and zebrafish. Upon activation, ADPGK knockout Jurkat T cells displayed increased cell death and ER stress. The increase in cell death resulted from a metabolic catastrophe and knockout cells displayed severely disturbed energy metabolism hindering induction of Warburg phenotype. ADPGK knockdown in zebrafish embryos led to short, dorsalized body axis induced by elevated apoptosis. ADPGK hypomorphic zebrafish further displayed dysfunctional glucose metabolism. In both model systems loss of ADPGK function led to defective N- and O-glycosylation. Overall, our data illustrate that ADPGK is part of a glucose sensing system in the ER modulating metabolism via regulation of N- and O-glycosylation.